Analisis Survey Merdeka Belajar Kampus Merdeka Terhadap Literasi Digital Pada Mahasiswa Fakultas Teknik Universitas Islam Nusantara - Luki Luqmanul Hakim; Yussi Perdana Saputra; Siti Nur (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The purpose of this study was to determine (1) student perceptions of the implementation of the MBKM curriculum that has been implemented at the Faculty of Engineering, Islamic University of Bandung, and (2) to determine student perceptions of digital literacy to support the success of MBKM. This research is a case study assisted by an online survey. Researchers collected data through an online survey via google form which was addressed to students of the Faculty of Engineering, Nusantara Islamic University, Bandung, as many as 655 students. The survey contains structured questions and leads to several answers that have been provided by the Ministry of Education and Culture as the compiler of the survey. The results showed that the implementation of MBKM at the Faculty of Engineering, Universitas Islam Nusantara was good, although the socialization that had been carried out by universities had not obtained maximum results. In addition, with regard to digital literacy, 94% of students stated that digital literacy is very important and strongly supports the MBKM program.